Design of Filing System for police investigation report on the Forensic Document Unit of POLRI Forensic Laboratory Center - Rochani Ani; Saeful Lukman; Bheta Agus Wardijono (Chemical Engineering Diponegoro University, 2019)
The Archiving system of Official Report of Inspection that runs on the Forensic Document Unit of POLRI Forensic Laboratory is particularly inefficient and effective as it still implements conventional filing systems. The recording of Official Report Documents is only in the general ledger. Based on these problems, the authors formulated